Implementasi Permendagri Nomor 77 Tahun 2020 Tentang Pengelolaan Keuangan Daerah pada Badan Pengelolaan Keuangan dan Pendapatan Daerah Provinsi Sulawesi Barat - Hasmuddin; Najmi Kamariah; Deasy Mauliana (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The implementation of Permendagri Number 77 of 2020 is an important step to ensure more transparent, accountable, and efficient regional financial management. However, the challenges faced in this implementation are quite complex, especially related to governance, information technology, and the quality of human resources of the apparatus. The purpose of this study is to analyze the implementation of Permendagri Number 77 of 2020 on the role of governance, information technology, and the quality of human resources of the apparatus to improve the performance of fund disbursement at the Regional Revenue and Financial Management Agency of West Sulawesi Province. The method used is a qualitative approach, with data collection methods through data collection, data collection instruments, data collection techniques and data analysis techniques. The results of the study have found that Governance in Regional Financial Management must be transparent in financial management starting from Financial Management documents, Budget Preparation documents to Audit Report Documents by the BPK and this can be easily accessed by the Public. Information technology (IT) has a very significant role in the modernization of regional financial management which has implemented SIPD in its entirety in presenting regional financial information. Human Resources (HR) play a crucial role in regional financial management, especially in the context of supporting applications such as SIPD. The process of disbursing funds in financial management requires compliance with strict procedures, from submitting applications to reporting accountability.